PENGEMBANGAN KOMPETENSI WIDYAISWARA DI TENGAH PANDEMI VIRUS CORONA 2019 - Taufik Karim (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2020)
This research aims to find first, the form of competency development in the midst of the corona virus pandemic 19, second, the development of learning management competencies and substantive competences in the corona virus pandemic 19. The research method used in this research is a mixed method of quantitative and qualitative research with a research sample of 50 respondents. Data collection techniques in research are literature review, questionnaire distribution using google form and interviews with training organizers as resource persons. The questionnaire distributed contains several questions which are allowed to choose more than 1 (one) answer. The data analysis technique used descriptive statistics and qualitative descriptive. The research results show that, first, the form of competency development that Widyaiswaya participated in during the corona virus pandemic 19 was a seminar / conference / workshop of 80%. Widyaiswara's competency development method prefers the E-learning method with the competency development supporting application used, namely the zoom meeting. Second, the development of technical competencies that is the focus is the development of Lecture's substantive competences. The development of substantive competencies needs to be adjusted to the needs of the times, such as mastering distance learning methods and using technology in order to achieve professional lecturers.